Subtract 3x^2 - 2x + 1 from 5x^2 + 3x -7

Answers

Answer 1
Answer: (5x^2 + 3x -7) - (3x^2 - 2x + 1)

5x^2 + 3x -7 - 3x^2 + 2x - 1

5x^2 - 3x^2 + 3x +2x - 7 - 1

2x^2 + 5x - 8
Answer 2
Answer: 5x^2 + 3x -7-(3x^2 - 2x + 1)=\n 5x^2+3x-7-3x^2+2x-1=\n 2x^2+5x-8

Related Questions

What is the value of the expression |x| + |y + z| when x = –6, y = –3, and z = –5?
Mrs. Colen took a trip. She drove 350 miles in 7 hours and 30 minuets. what is her average speed to the nearest tenth of a mile per hour
On discovering that her family had a 70% risk of heart attack, Erin took a treadmill test to check her own potential of having a heart attack. The doctors told her that the reliability of the stress test is 67%. What is the probability that Erin will not have a heart attack and the test predicts that she will?
Can this be simplified
Please give an accurate answer and show work.

Solve the equation for y:
2x + 5y = 20

Answers

Answer:

y = (20-2x)/(5)

Step-by-step explanation:

Given

2x + 5y = 20 ( isolate the term in y by subtracting 2x from both sides )

5y = 20 - 2x ( divide both sides by 5 )

y = (20-2x)/(5)

The Answer will be y=4

A baseball player had 4 hits in 8 games. At this rafe, how many hits will the baseball player have in the next 28 games?

Answers

Answer: About 14 hits

How do I answer 16 in scientific notation? Please help!

Answers

Move the decimal place over 9 places to the right for the numerator

9,900,000,000

Move the decimal place over 8 places to the right for the denominator

150,000,000

Divide both

9,900,000,000 / 150,000,000 = 66


What is the intermediate step in form (x+a)^2=b as a result of completing the square of the following equation6x^2+72x-170=-2

Answers

Answer:

6x² + 72x - 170 = -2

<=> 6x² + 72x - 168 = 0

<=> x² + 12x - 28 = 0

<=> x² + 12x + 36 = 64

<=> (x+6)² = 64

Step-by-step explanation:

I can't figure this equation out, help!!!!!!!!!!!!!!!!!!!!!!!***The answer is 1 and -0.5, but I just can't figure out how to work it out.***

Answers

(4)/(2x-1)-(2)/(x)=2;\ D:2x-1\neq0\ \wedge\ x\neq0\Rightarrow x\neq(1)/(2)\ \wedge\ x\neq0\n\n(4)/(2x-1)=2+(2)/(x)\n\n(4)/(2x-1)=(2x)/(x)+(2)/(x)\n\n(4)/(2x-1)=(2x+2)/(x)\n\ncross\ multiply\n\n(2x-1)(2x+2)=4x\n4x^2+4x-2x-2-4x=0\n4x^2-2x-2=0\n4x^2-4x+2x-2=0

4x(x-1)+2(x-1)=0\n(x-1)(4x+2)=0\iff x-1=0\ \vee\ 4x+2=0\nx=1\in D\ \vee\ x=-(1)/(2)\in D\n\nSolutions:x=-(1)/(2)\ or\ x=1.

Day and Night Kennel charges $20 per day plus a food fee of $15 to board a pet. Home Away From Home Kennel charges $30 per day plus a food fee of $5. Which system represents this real-world situation?

Answers

Let,

"p" represent the total cost to board the pet (food fee + charge per day included)
"d" represent the total number of days to board the pet

Now,
$$The equation to find how much Day and Night Kennel chargers :
$$ p\ =\ 20d+15

$$The equation to find how much Home Away From Home Kennel :
$$ p\ =\ 30d+5



Answer:

Answer is (B)!!

Step-by-step explanation:

These people that have the green check are such a waste of time...

UW